Vertical Structure of Katabatic Winds in Mizuho Plateau - Kobayashi, S. (1978)
P(論文) Observation of vertical structure of katabatic winds blowing in Mizuho Plateau was made by means of radio sondes. It was found that the layer of the katabatic winds is roughly identical with the surface inversion layer. The surface inversion layer showed seasonal variations in thickness and intensity. The katabatic wind layer disappeared when a cyclone was passing over the ocean in the vicinity of Syowa Station, as noticed from the disarranged wind speed profiles. Wind vectors in the lowest few hundred metres of the katabatic wind layer showed that a thermal wind persisted in the surface inversion layer. Therefore, the katabatic winds in Mizuho Plateau may be called the "inversion winds", because they are essentially controlled by the thermal wind due to the existence of a sloped inversion layer. departmental bulletin paper